The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.21814/rpe.19130
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de jogos educativos no ensino de conteúdos acadêmicos: Uma revisão sistemática da literatura

Abstract: Este estudo teve como objetivo fazer uma revisão sistemática da literatura de estudos empíricos que avaliaram o efeito de jogos educativos na aprendizagem de assuntos acadêmicos, comparando os efeitos de estudos com diferentes delineamentos de pesquisa. Na revisão, foram incluídos artigos empíricos e relatos de casos publicados em inglês ou português, de janeiro de 2006 a setembro de 2019, que mencionavam ou continham palavras-chave definidas previamente que avaliavam os jogos como método de intervençã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
1
0
2
Order By: Relevance
“…Pinheiro and Pinheiro (2021), Borges (2019), Silva, Oliveira and Silva (2020) state that in school environments the use of games in a contextualized manner can represent an extraordinary instrument in working with different contents, helping educators as a method of intervention for the teaching of formal educational content. Tsutsumi et al (2020), in a systematic literature review of empirical studies that evaluated the effect of educational games on learning academic subjects, demonstrated that games had the effect of increasing the academic performance of students. For Santos et al (2021), educational games instigate the student's attitude of protagonism, guaranteeing them a more meaningful learning.…”
Section: Discussionmentioning
confidence: 99%
“…Pinheiro and Pinheiro (2021), Borges (2019), Silva, Oliveira and Silva (2020) state that in school environments the use of games in a contextualized manner can represent an extraordinary instrument in working with different contents, helping educators as a method of intervention for the teaching of formal educational content. Tsutsumi et al (2020), in a systematic literature review of empirical studies that evaluated the effect of educational games on learning academic subjects, demonstrated that games had the effect of increasing the academic performance of students. For Santos et al (2021), educational games instigate the student's attitude of protagonism, guaranteeing them a more meaningful learning.…”
Section: Discussionmentioning
confidence: 99%
“…Abdul Jabbar e Felicia [2015] concluem que GBL "ajuda os estudantes a desenvolver habilidades [skills] e conhecimento e fortalece sua habilidade de tratar as experiências de aprendizado fornecida pelos jogos". Já Tsutsumi et al [2020] encontram 24 estudos que mostram que os "os jogos tiveram o efeito de aumentar o desempenho acadêmico de alunos". Mais recentemente, S. B.…”
Section: Motivaçãounclassified
“…Já Silva e Moraes (2011) destacam que os jogos de regras podem ser adaptados ou mesmo elaborados para um fim específico nas instituições escolares. Segundo as autoras deve-se usar esse mecanismo para a promoção de um conceito ou habilidade do currículo escolar.4.realizar uma revisão sistemática da literatura sobre o uso de jogos para ensino de conteúdos acadêmicos,Tsutsumi et al (2020) identificaram que a maior parte dos estudos, publicados de forma gratuita, aponta que a matemática é a disciplina mais usada na elaboração de jogos. No entanto,…”
unclassified